Oxygen Vacancies Allow Tuning the Work Function of Vanadium Dioxide. Issue 22 (3rd October 2018) - Wang, Rongbin; Katase, Takayoshi; Fu, Ke‐Ke; Zhai, Tianshu; Yang, Jiacheng; Wang, Qiankun; Ohta, Hiromichi; Koch, Norbert; Duhm, Steffen
Abstract: The evolution of electron valence bands, core levels, and work function of vanadium dioxide (VO2 ) thin films upon argon ion sputtering and annealing, as commonly done to obtain atomically clean surfaces, with and without low‐pressure oxygen atmosphere during annealing is investigated by ultraviolet and X‐ray photoemission spectroscopy. Both sputtering and annealing in vacuum introduce lower oxidation state V species, leading to an increased intensity of V 3d derived bands close to the Fermi level. Such oxygen deficient surfaces exhibit low work function values as low as 4.40 eV. Annealing the sample under low‐pressure oxygen atmosphere (few times 10 −4 mbar partial O2 pressure) results in stoichiometric VO2 surfaces with a high work function of up to 6.70 eV. Moreover, the work function of the VO2 can be continuously tuned between the high and low limits by adjusting the atomic ratio of oxygen and vanadium at the surface. Appropriately adjusted VO2 can thus be employed as moderate electron as well as superior hole injecting electrode material in electronic and optoelectronic devices. Abstract : The work function of vanadium dioxide (VO2 ) thin films can be controlled by the amount of oxygen vacancies close to the surface and cover a wide range from 4.40 to 6.70 eV. Appropriately adjusted VO2 can thus be employed as moderate electron as well as superior hole injecting electrode material in (opto‐)electronic devices.